Image Retrieval in Spatial and Temporal Domains With a Quadrant Detector - Ming-Jie Sun; Wen Chen; Teng-Fei Liu; Li-Jing Li (IEEE Photonics Journal, 2017)
To retrieve an N pixel image of a scene, conventional digital cameras record the information using an N pixelated detector with one measurement, while single-pixel imaging achieves it by sampling the image in a particular basis and recording the light intensities of N temporal measurements with a single-pixel detector. Besides these two schemes, it is also possible to obtain the same spatial information with an X pixels detector and N/X measurements, where the pressure of information retrieval is distributed to both spatial and temporal domains, rather than condensed in one domain. In this paper, we investigate this possibility and present a 4-pixels imaging scheme, which retrieves an image partially in spatial domain and partially in temporal domain, by adopting a quadrant detector to a single-pixel imaging system. While yielding images with equal quality, the proof-of-principle system we built is four times faster than a standard single-pixel imaging system, demonstrating the feasibility of the proposed scheme. Our work exploits the flexibility of space-time information retrieval and can be useful for applications where comprise between spatial and temporal domains is needed.